Pengaruh Kompensasi, Lingkungan Kerja Non Fisik, dan Motivasi Kerja Terhadap Kepuasan kerja Karyawan - Putri Pande, Ni Nyoman Paramita Iswari; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 3 No 7 (2014), 2014)
This study aims to determine the effect of compensation, non-physical work environment, and work motivation on employee job satisfaction either simultaneously or partial, as well as independent variables to determine which one has the most impact on employee job satisfaction. This research was conducted at the World Brand Factory (WBF) Company's Kuta-Bali. The number of respondents in this study were 51 employees. Data collected through interviews, observations, and the distribution of questionnaires. The analysis technique used is multiple linear regression. Based on the results of the analysis found that compensation, non-physical work environment, and work motivation simultaneously positive and significant effect on employee job satisfaction. Compensation, non-physical work environment, and work motivation of each partial has a positive and significant effect on employee job satisfaction. Among the three independent variables, the variable compensation have the greatest influence on employee job satisfaction. Keywords : compensation, non-physical work environment, work motivation, job satisfaction
Keywords: compensation , non-physical work environment, work motivation, job satisfaction